Psychosocial factors and burnout among oncology nurses in Brunei Darussalam: A pilot study - Jais, Fatin Afiqah; Yan Choo, Teo; Kahan, Hasnan; Shahbudin, Shanti; Abdul-Mumin, Khadizah H; Rahman, Hanif Abdul (Belitung Nursing Journal, 2021)
Background: Existing evidence showed that adverse psychosocial factors contribute to burnout in oncology nurses and impose profound implications to nursing practice. Due to the complexity of this relationship, more studies are still needed. Objective: To investigate the prevalence and relationship between burnout and psychosocial factors among oncology nurses. Methods: A descriptive cross-sectional study design was conducted in 2018 using the Maslach Burnout Inventory and the Copenhagen Psychosocial Questionnaire to measure burnout and psychosocial factors, respectively. Descriptive and multivariate regression using maximum likelihood procedures were used for analysis. Results: Out of three burnout variables, emotional exhaustion demonstrated a highly significant relationship towards psychosocial factors, particularly quality of leadership (p <0.001), justice and respect (p <0.001), and rewards (p <0.001) – congruent to a high prevalence of emotional exhaustion reported. Conclusion: Improvement in leadership quality, rewards, justice and respect could minimise emotional exhaustion among oncology nurses. These findings further inform management and policymakers to target these specific psychosocial factors in addition to using other interventions to counter the harmful effects of burnout. A positive psychosocial workplace would consequently decrease the risk of nurses’ intention to leave, reduce nurse shortages, and increase the quality of patient care.